2004
DOI: 10.1261/rna.5650904
|View full text |Cite
|
Sign up to set email alerts
|

Modifications and deletions of helices within the hairpin ribozyme–substrate complex: An active ribozyme lacking helix 1

Abstract: Within the hairpin ribozyme, structural elements required for formation of the active tertiary structure are localized in two independently folding domains, each consisting of an internal loop flanked by helical elements. Here, we present results of a systematic examination of the relationship between the structure of the helical elements and the ability of the RNA to form the catalytically active tertiary structure. Deletions and mutational analyses indicate that helix 1 (H1) in domain A can be entirely elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…For the HCH and HS 6 H junction variants, TOPRNA quantitatively predicts the experimentally measured difference in docking free energy relative to the HHHH junction ( 6 ). Our simulations also corroborate the observation that the ribozyme is tolerant of base pair deletions in the A and B helices ( 42 ), and provides a physical explanation for why helix A but not helix B frays in the 2WJ hairpin ribozyme ( 38 , 39 ). Collectively, this agreement strongly argues that topological constraints imposed by the central junction are a key contributor to the docking stability of the hairpin ribozyme.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For the HCH and HS 6 H junction variants, TOPRNA quantitatively predicts the experimentally measured difference in docking free energy relative to the HHHH junction ( 6 ). Our simulations also corroborate the observation that the ribozyme is tolerant of base pair deletions in the A and B helices ( 42 ), and provides a physical explanation for why helix A but not helix B frays in the 2WJ hairpin ribozyme ( 38 , 39 ). Collectively, this agreement strongly argues that topological constraints imposed by the central junction are a key contributor to the docking stability of the hairpin ribozyme.…”
Section: Discussionsupporting
confidence: 83%
“…Thus, while a HHHH topology biases the junction towards docking-competent conformations, it is not particularly optimized for orienting the A and B loops in the correct register. Experimental studies have also observed that the hairpin ribozyme is tolerant of shortening the A and B helices ( 42 ).…”
Section: Resultsmentioning
confidence: 99%